Pancasila Student Profiles in Science Lessons and Potential for Strengthening by Developing PjBL-Based E-Modules - Imania, Yayang Fatma; Marwoto, Putut; Ellianawati, Ellianawati (Physics Communication, 2022)
This study aims to find out class VII students’ profiles of Pancasila abilities of MTs SA Miftahul Huda Bumijawa. The dimensions of the meticulous Pancasila student profiles include four dimensions, namely critical reasoning, creativity, mutual cooperation, and independence. This type of research is a qualitative descriptive. Data collection instrument were observation and interview guidelines. Based on research data, the results showed that the ability of students to the Pancasila student profiles were still very low. 70% of students were in category of very low and another 30% were in category of low on the critical reasoning dimension. 57% of the students were in category of very low and another 43% were in category of low on the independent dimension. Overall students where in category of very low on the dimensions creative and mutual cooperation dimensions. It indicates that the applied learning media and learning models have not been able to strengthen Pancasila student profiles. The Integrated Science learning process still uses conventional methods and rarely does practicum or projects. The media used is still limited to textual. One of the potential solutions in order to strengthen the Pancasila student profiles are to develop an e-module based PjBL.